Pengaruh Terpaan Iklan Layanan Masyarakat, Penggunaan Media Sosial Facebook, Dukungan Keluarga, Dukungan Lingkungan Kerja terhadap Tingkat Keberhasilan Ibu Bekerja Memberi ASI Eksklusif - Kurniasari, Andra Fatma (Interaksi: Jurnal Ilmu Komunikasi, 2016)
Abstract            This study examine exposure of public service announcements, facebook, family support, and company support which is involving working mom to have exclusive breastfeeding. The coefficient determination of this study is 70,2. It shows that all of variables affect the successfully working mom giving exclusive breastfeeding. This study also verified the Social Learning Theory, Social Marketing concept, Dynamic Social Impact Theory, and Social Support Theory.  Keywords: Working Mom, Exclusive Breastfeeding, Exposure Public Service Announcements